Madarosis in a normolipidemic woman: Is giant xanthelasma palpebrarum the culprit? - Saloni Desai; Hari Pathave; Abigail Syiemlieh; Chitra Nayak (Wolters Kluwer Medknow Publications, 2022)
Xanthelasma palpebrarum (XP) is the most common cutaneous xanthoma. It is triggered by hyperlipidemia, thyroid dysfunction, and diabetes mellitus. Madarosis, loss of eyebrows, occurs in various diseases ranging from local dermatological disorders to complex systemic diseases. Herein, we present a case of giant XP in a middle-aged female in whom bilateral partial madarosis developed. In polarized contact dermoscopy, the number of hairs on xanthoma plaque was reduced compared to normal.